(3eDSSh GdOhd GdESdGejI (B/s (3eYLe TGed jMJhj Ydi JQGLe eDSSj GdOhd GdESdGejI efP JCSjS Chd OhdI ESdGejI aj GdeOjfI GdefhQI Gdi fgGjI GdbQf GdYTQjf (B.s - (3GdSjO, aDGO UGdMs ((3HjQhJ (B:s (3ecJHI MSf GdYUQjI,s, 2011)
(3eYLe LGeY TGed jMJhj Ydi JQGLe eDSSj GdOhd GdESdGejI efP JCSjS Chd OhdI ESdGejI aj GdeOjfI GdefhQI Edi fgGjI GdbQf GdYTQjf(B.s
(3jTJed Ydi cTGaGJ(B.s
Keywords: (3GdHdGO GdESdGejIs -- (3edhc hMcGes -- (3JQGLes -- (3eYGLes